Die Rolle von Ankunftsräumen für die Integration Zugewanderter. Eine kritische Diskussion des Forschungsstandes - Hans, Nils; Hanhörster, Heike; Polívka, Jan; Beißwenger, Sabine (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
The many new forms of migration and the increasing diversification of our societies are leaving their mark on urban spaces. In the arrival spaces featuring high levels of migrants, we tend also to find higher levels of poverty, irrespective of whether the households concerned have a migration background or not. Such neighbourhoods, often referred to in Germany as "migrant neighbourhoods" or "ethnic colonies", have long been a focus of geographic and sociological urban research. Closely connected with such neighbourhoods is the discussion over context effects and their potential to create disadvantage. The starting point for this paper is the observation that most research into such context effects highlights deficits, without taking sufficient account of those factors and mechanisms influencing migrants' access to societal resources. The article thus takes a look at available empirical and theoretical research, highlighting three current aspects influencing such access in arrival spaces: the increasingly multi-local contacts of these migrants, the specific concentration of migrant-related opportunity structures in certain sub-districts of our cities, and governance processes reacting to increasing diversity and constantly changing needs. Currently predominantly focused on ring-fenced neighbourhoods, the article aims to further integration research, calling for greater priority to be attached to looking at the day-to-day lives and practices of migrants. The characteristics and dynamics of arrival spaces illustrate the growing permeability of spatial and social structures, highlighting the need to think out of the neighbourhood box when discussing integration.
Keywords: Arrival spaces; Migration; (Super-)Diversity; Neighbourhood effects; Immigrant integration; Cross-local ties; Opportunity structures